2012
DOI: 10.1128/cvi.00058-12
|View full text |Cite
|
Sign up to set email alerts
|

Live Oral Typhoid Vaccine Ty21a Induces Cross-Reactive Humoral Immune Responses against Salmonella enterica Serovar Paratyphi A andS. Paratyphi B in Humans

Abstract: ABSTRACTEnteric fever caused bySalmonella entericaserovar Paratyphi A infection has emerged as an important public health problem. Recognizing that in randomized controlled field trials oral immunization with attenuatedS. entericaserovar Typhi live vaccine Ty21a conferred significant cross-protection againstS. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 74 publications
(90 reference statements)
2
73
0
Order By: Relevance
“…The levels of antibodies to LPS have been shown to rise within the first 2 weeks following immunization with live oral typhoid vaccines (25,29,(36)(37)(38)(39)(40)(41)(42). Therefore, we explored whether the functional activity of antibodies described above correlated with anti-LPS titers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The levels of antibodies to LPS have been shown to rise within the first 2 weeks following immunization with live oral typhoid vaccines (25,29,(36)(37)(38)(39)(40)(41)(42). Therefore, we explored whether the functional activity of antibodies described above correlated with anti-LPS titers.…”
Section: Resultsmentioning
confidence: 99%
“…The measurement of strain-specific humoral immune responses, including antibody-secreting cells (ASC) and/or serum antibodies, is a fundamental part of assessing the immunogenicity of live oral Salmonella vaccines. Ty21a and other candidate typhoid vaccines (including CVD 909) are capable of eliciting S. Typhi-specific antibodies (e.g., against O and H antigens) (25,29,36,39,41,43,44), as well as cross-reactive antibodies against S. Paratyphi A and S. Paratyphi B (29). Nevertheless, the role of such antibodies, if any, in protection from disease or in the elimination of intracellular bacteria is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ty21a is a live attenuated bacterial strain that provides high-level durable protection against endemic typhoid fever. Additionally, there is evidence that Ty21a confers cross-protection against enteric fevers caused by Salmonella enterica serovar Paratyphi B (15) and provides crossreactive immune responses against S. enterica serovar Paratyphi A (16,17). Previously, we showed that Ty21a expressing S. sonnei or S. dysenteriae O-antigens provided robust immunity against virulent Shigella challenge in mice (13,18).…”
mentioning
confidence: 99%